Propuesta de mejoramiento para la gestión de recursos humanos y del tiempo en el departamento de ingeniería de prueba y ensamble en la empresa componentes Intel De Costa Rica S.A. - Zawadzki-Wisniewski, Juan Pablo (Instituto Tecnológico de Costa Rica, 2011)
Intel Corporation is one of major renowned multinational companies in the world and the number one in the microprocessors manufacturing process for servers and personal computers, either desktop or mobile, among other things. Big part of this success is due to the operating process excellence, independently of the geographical location and the country’s culture where the process is performed. However, great improvement possibilities have been identified at project level, mainly due to the formal project management differences between manufacturing sites and even between departments and work groups. The main objective of this investigation was to provide a project management improvement proposal that will allow progressively reach the level of excellence expected by the company and the corporation in all of his work activities, either operational or services and projects. This investigation was held in the company “Componentes Intel de Costa Rica S.A.”, specifically in the process engineering department. The department’s management, based in the business needs, the mission and vision of this group, and the recommendations made by the project’s office inside the department, has defined as a priority to emphasize this investigation on the time and resource management knowledge areas, at the formal project management level. The improvement proposal presented was structured based in four main deliverables: current state investigation of the department in the formal project management processes, definition of the ideal state of this group at project’s level, gap analysis between those two states, and the generation of recommendations in order to improve the project administration processes. The methodology used was based in a descriptive type investigation, analyzing study variables through interviews and documents compilation, as the standardization and the project’s control and follow up processes; that allowed obtaining concrete results related to the two knowledge areas defined. Making usage of the obtained results and the analysis performed following the PMI guides, the deliverables defined for this investigation were developed and completed. Among the main conclusions obtained were the big improvement opportunities related to the processes’ standardization, the real performance measurement and the development plans for the department’s personnel at project level. A great advantage the process engineering department has is its project’s office recently instituted, key for the development and monitoring of the improvement plans at project level. The most important recommendations of this work were oriented in taking advantage of the infrastructure and tools available inside the company to improve the department’s project management, and also to focus on using the guides and best practices established by the PMI, or other international organisms recognized in project management success. The present investigation had the main intention to create an improvement proposal for the process engineering department in relation with the project management, aligned with the corporative vision, in order to be part of the continuous improvement efforts in this area.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2011.
Keywords: Responsabilidad administrativa; Gestión del tiempo; Conocimiento; Estandarización; Microprocesadores; Procesos